2021
DOI: 10.5194/acp-21-6919-2021
|View full text |Cite
|
Sign up to set email alerts
|

Microphysical processes producing high ice water contents (HIWCs) in tropical convective clouds during the HAIC-HIWC field campaign: evaluation of simulations using bulk microphysical schemes

Abstract: Abstract. Regions with high ice water content (HIWC), composed of mainly small ice crystals, frequently occur over convective clouds in the tropics. Such regions can have median mass diameters (MMDs) <300 µm and equivalent radar reflectivities <20 dBZ. To explore formation mechanisms for these HIWCs, high-resolution simulations of tropical convective clouds observed on 26 May 2015 during the High Altitude Ice Crystals – High Ice Water Content (HAIC-HIWC) international field campaign based out of Cayenne,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 65 publications
1
18
1
Order By: Relevance
“…The radar microphysical retrieval techniques in ice are still in the process of evaluation and refinement using in situ microphysical airborne and surface observations. However, we believe that Equations 5-10 used in this study is a good first attempt because they produce results consistent with occasional in situ measurements in the proximity of the polarimetric radars (e.g., Murphy et al, 2020;Nguyen et al, 2019;Ryzhkov et al, 1998) and which are in a ballpark of the majority of airborne probes' measurements of IWC, D m , and N t reported in the literature (e.g., Finlon et al, 2019;Heymsfield et al, 2013Heymsfield et al, , 2015Heymsfield et al, , 2017Huang et al, 2021;Leroy et al, 2017;McFarquhar et al, 2007;Stechman et al, 2020). As mentioned before, our retrieved D m is the ratio of the fourth and third moments of the size distribution of equivolume diameters which is different from D mm or median volume (D mv ) size commonly estimated from in situ airborne microphysical probes which measure a maximal particle dimension.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The radar microphysical retrieval techniques in ice are still in the process of evaluation and refinement using in situ microphysical airborne and surface observations. However, we believe that Equations 5-10 used in this study is a good first attempt because they produce results consistent with occasional in situ measurements in the proximity of the polarimetric radars (e.g., Murphy et al, 2020;Nguyen et al, 2019;Ryzhkov et al, 1998) and which are in a ballpark of the majority of airborne probes' measurements of IWC, D m , and N t reported in the literature (e.g., Finlon et al, 2019;Heymsfield et al, 2013Heymsfield et al, , 2015Heymsfield et al, , 2017Huang et al, 2021;Leroy et al, 2017;McFarquhar et al, 2007;Stechman et al, 2020). As mentioned before, our retrieved D m is the ratio of the fourth and third moments of the size distribution of equivolume diameters which is different from D mm or median volume (D mv ) size commonly estimated from in situ airborne microphysical probes which measure a maximal particle dimension.…”
Section: Discussionsupporting
confidence: 61%
“…French Guiana show generally higher values of IWC and N t and lower values of D mm in ice compared to the continental midlatitude MCSs Leroy et al (2017). reported IWC varying from 0.5 to 2.5 g m −3 and D mm in the range between 0.25 and 0.7 mm in the Darwin flights Huang et al (2021). found very similar ranges of IWC and D m during the flights in Cayenne and noted quite high total number concentrations N t between 100 and 200 L −1 .…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…conducted high-resolution simulations of tropical convection and found significant overestimates of radar reflectivity and underestimates of total ice crystal concentration (N i ). Adding SIP in high-resolution simulations, Huang et al (2022) found a significant improvement in simulated N i compared with the in situ observations.…”
Section: Introductionmentioning
confidence: 86%
“…Over the last few years, there have been many new efforts based on systematic studies of the effect of SIP on cloud microphysics with the help of cloud simulations (e.g., Phillips et al, 2017Phillips et al, , 2018Sullivan et al, 2018;Hoarau et al, 2018;Fu et al, 2019;Sotiropoulou et al, 2020Sotiropoulou et al, , 2021Dedekind et al, 2021;Hawker et al, 2021;Huang et al, 2021Huang et al, , 2022and others). Most of these modelling efforts have been focused on matching simulated moments of particle size distributions (PSDs) with those observed in situ.…”
Section: Introductionmentioning
confidence: 99%